Forecasting Cerdas: Kunci Sukses Bisnis - Mohamad Chaidir; Ruslaini Ruslaini; Shinta Amelia (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2025)
This research examines the role of intelligent forecasting as a key element in modern business success. By leveraging artificial intelligence (AI) technology, big data analytics, and machine learning, intelligent forecasting enables companies to predict market trends and optimize strategic decision-making. The research method was conducted through online webinars involving academics, practitioners, and business actors. The results showed that intelligent forecasting could improve accuracy by up to 98.2% and prediction ratio by 96.5%. However, MSMEs still face challenges in adopting this technology, including limited resources and technological understanding. This research concludes that intelligent forecasting is vital in improving operational efficiency and business competitiveness, but a more inclusive approach is needed to ensure wider adoption across various business scales.